Isometamidium concentrations in the sera of cattle maintained under a chemoprophylactic regime in a tsetse-infested area of Zimbabwe - Eisler, M.C.; Maruta, J.; Nqindi, J.; Connor, R. J.; Ushewokunze‐Obatolu, U.; Holmes, P.H.; Peregrine, A.S. (Wiley, 1996)
An experiment was carried out to determine the concentrations of the trypanocidal drug isometamidium chloride in the sera of cattle maintained under a chemoprophylactic regimen at Rekomitjie, Zimbabwe, an area of high tsetse challenge in the Zambezi valley. In February 1993, 24 cattle at this site were treated intramuscularly with isometamidium chloride at a dose of 1.0 mg/kg body weight. Thereafter all animals were monitored regularly for 6 months for the presence of trypanosomes and sera were collected to determine the concentrations of isometamidium using an ELISA. Isometamidium treated cattle appeared to be protected against trypanosome infections for at least 18 weeks following treatment. Thereafter, three trypanosome infections were detected, between 20 and 22 weeks following treatment. In contrast, in 18 untreated control cattle at the same site, 9 trypanosome infections were detected over the first 18 weeks of the experiment. Quantification of the isometamidium concentration in sera from the drug treated cattle indicated that the apparent half‐life of isometamidium in these animals was 23 days. This was similar to the half‐life observed previously in cattle treated under laboratory conditions. The isometamidium ELISA was shown to be capable of quantifying drug levels in 20 out of 23 cattle for at least 70 days after treatment. There was no evidence of drug resistant trypanosomes at this site.